Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd008492.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-based combination therapy for treating uncomplicatedPlasmodium vivaxmalaria

Abstract: BackgroundPlasmodium vivax is an important cause of malaria in many parts of Asia and South America, and parasite resistance to the standard treatment (chloroquine) is now high in some parts of Oceania. This review aims to assess the current treatment options in the light of increasing chloroquine resistance. ObjectivesTo compare artemisinin-based combination therapies (ACTs) with alternative antimalarial regimens for treating acute uncomplicated P. vivax malaria. Search methodsWe searched the Cochrane Infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…While the choice of partner drug may also affect posttreatment gametocytemia prevalence, as SP monotherapy is associated with increased posttreatment gametocytemia (17,22), our observations were similar to those observed for other combination therapies elsewhere (17,23). We measured the effect of primaquine through gametocyte clearance, the number of gametocyte-weeks of circulation, and the area under the curve using gametocyte density over time.…”
Section: Discussionsupporting
confidence: 66%
“…While the choice of partner drug may also affect posttreatment gametocytemia prevalence, as SP monotherapy is associated with increased posttreatment gametocytemia (17,22), our observations were similar to those observed for other combination therapies elsewhere (17,23). We measured the effect of primaquine through gametocyte clearance, the number of gametocyte-weeks of circulation, and the area under the curve using gametocyte density over time.…”
Section: Discussionsupporting
confidence: 66%
“…We confirm that DHA/PPQ acts faster ( < 48 h) than chloroquine (≈72 h) in eliminating sexual and asexual P. vivax parasites and that DHA/PPQ provides an excellent postexposure prophylaxis against potential recurrences for > 2 months ( 11 ). This benefit relies on the combination of artemisinin derivatives (DHA), which are fast-acting drugs capable of eliminating any P. vivax blood stages, and a long-lasting partner drug (PPQ), which has a long terminal elimination half-life and is highly effective in preventing P. vivax recurrence for up to 56 days.…”
Section: Discussionsupporting
confidence: 59%
“…The combination of dihydroartemisinin-piperaquine (DP) has been assessed in clinical trials for almost a decade, and shown to be highly efficacious against both Plasmodium falciparum and P. vivax infections [3],[9],[10]. Since 2010, DP has been recommended by WHO for the treatment of uncomplicated falciparum malaria [5], providing a promising alternative to other currently available ACTs, based upon its high efficacy, excellent safety profile, once daily dosing scheme, and prolonged post-treatment prophylactic protection [11][13].…”
Section: Introductionmentioning
confidence: 99%